The impact of N, N′-ditopic ligand length and geometry on the structures of zinc-based mixed-linker metal–organic frameworks. Issue 37 (18th September 2017) - Burrows, Andrew D.; Chan, Siobhan; Gee, William J.; Mahon, Mary F.; Richardson, Christopher; Sebestyen, Viorica M.; Turski, Domenyk; Warren, Mark R.
Abstract : A series of MOFs containing di(4-pyridyl)-1 H -pyrazole linkers have been prepared and characterised. Abstract : Combining Zn(NO3 )2 ·6H2 O with a series of dicarboxylic acids in the presence of the N, N ′-ditopic ligand di(4-pyridyl)-1 H -pyrazole (Hdpp) results in a series of mixed-linker metal–organic frameworks (MOFs) that have been crystallographically characterised. The reaction with 1, 4-benzenedicarboxylic acid (H2 bdc) gives [Zn2 (bdc)2 (Hdpp)2 ]·2DMF1, which shows Zn2 (μ-carboxylate)2 (carboxylate)2 secondary building units (SBUs) linked by bdc ligands into sheets, and these are pillared by the Hdpp linkers into a doubly-interpenetrated three-dimensional network. The reaction with 1, 4-naphthalene dicarboxylic acid (H2 ndc-1, 4) gives two products: [Zn2 (1, 4-ndc)2 (Hdpp)]·4DMF2a forms a three-dimensional network in which sheets, formed from Zn2 (carboxylate)4 'paddle-wheel' SBUs being linked by 1, 4-ndc, are connected together by Hdpp pillars, whereas [Zn(1, 4-ndc)(Hdpp)]·DMF2b forms a fourfold interpenetrated structure based on diamondoid networks with single zinc centres as nodes. The reaction with 1, 3-benzenedicarboxylic acid (H2 mbdc) produces [Zn(mbdc)(Hdpp)]·DMF3, which forms a two-dimensional network with (4, 4) topology in which ZnO2 N2 nodes are interlinked by mbdc and Hdpp linkers. The reaction with 5-methyl-1, 3-benzenedicarboxylic acid (H2 mbdc-Me) also forms a two-dimensional network structure, [Zn2 (mbdc-Me)2 (Hdpp)2 ]·DMF4, albeit wherein dicarboxylates bridge between zinc-dicarboxylate tapes, themselves formed by interlinking of Zn2 (μ-carboxylate)2 (carboxylate)2 SBUs similar to those in1 . Finally, the reaction with 2, 6-naphthalene dicarboxylic acid (H2 ndc-2, 6) yields two crystalline species, both having the formula [Zn2 (2, 6-ndc)2 (Hdpp)]·DMF5a /5b and possessing infinite zinc-carboxylate chain motifs interlinked by both naphthalene rings and Hdpp linkers into a three-dimensional framework. In compounds1, 2b, 3 and4, the pyrazole NH groups are involved in hydrogen bonding that serves to link either interpenetrated networks or neighbouring sheets together. However, in2a and5a /5b the NH groups project into the pores of the framework enabling interactions with guest molecules.